Equity throughout the life course and the evolving role of the Pan American Health Organization - Betzabé Butrón Riveros; Marilyn Rice; Cristiana Toscano; Maria Pilar Campos Esteban; Pablo Duran; Gerry Eijkemans; Suzanne Serruya; Enrique Vega; Martha Velandia-González; Luis Andres de Francisco (Pan American Health Organization, 2023)
The objective of this article is to summarize the evolution of the regional commitments of the Pan American Health Organization (PAHO) on health promotion and strategies to improve the health and well-being of women, children, adolescents, and older persons. PAHO regional strategies approved by Member States in the last 20 years are used as the main source of information. The article presents the challenges of making health promotion a public health strategy widely applied in the Region of the Americas and the efforts to renew Member States' collective actions. The article also describes current PAHO efforts to include the positive aspects of health (i.e., well-being, optimal development, and functional ability) and the life course approach as opportunities to advance equity. The article reflects on immunization as a public good and the urgency to address the current challenges as a core element of the regional efforts to transform health systems after more than two years of the COVID-19 pandemic.